Analysis of studies and researches on the social meaning of the University for All Program (PROUNI) - Casali, Alipio Marcio Dias (2015)
This study addresses the social meaning of the University for All Program (PROUNI), in the context of educational policies in Brazil. It presents a systematization of the academic and scientific productions on the Program (2006–2011) and its prospects. The survey records obtained from the Scientific Electronic Library Online (SciELO) and the Public Domain Portal CAPES scored a total of 27 dissertations, theses, and scientific articles published in eight Brazilian states, mostly in the southeast, in 2009. Four subthemes were analyzed: policies related to access to and training in higher education, social inclusion policy, tax breaks, and perceptions and impacts on the beneficiaries. This study concludes that the PROUNI, a public policy of affirmative action, has a relevant social meaning and wide cultural and historical significance and, as such, is obstructed by conflicts and contradictions with tax breaks and the lack of attention to the beneficiaries being its most controversial issues.